1991
DOI: 10.2307/2444956
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence for the Origin of the S-derived Genomes of Polyploid Triticum Species

Abstract: The genus Triticum includes several polyploid species that arose due to hybridization between two or more diploid species. Section Sitopsis is comprised of five diploid species given the genome designation S. Four polyploid species are recognized that contain an S or S-derived genome. We have used two repetitive DNA sequences found primarily in the S genomes of Triticum to determine the likely diploid progenitors of the polyploid species. Comparison of restriction fragments that hybridize to probes for these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…bicornis. This agrees with the widely accepted classification of the section based on isoenzymes (Jaaska 1978), electrophoresis of seedling proteins (Bahrman et al 1988), cpDNA (Bowman et al 1983;Ogihara and Tsunewaki 1988;Wang et al 1997), rRNA (Dvorak 1990), repetitive DNA sequences (Talbert et al 1991), variation in the restriction patterns of repeated nucleotide sequences (Dvorak and Zhang 1992), electrophoresis of leaf proteins (Mendlinger and Zohary 1995), nRFLP (Sasanuma et al 1996;Ciaffi et al 2000;Giorgi et al 2002), in situ hybridisation (Giorgi et al 2003), and CAPS on cpDNA (Haider and Nabulsi 2008).…”
Section: Genetic Relationships Among Triticum Speciessupporting
confidence: 86%
“…bicornis. This agrees with the widely accepted classification of the section based on isoenzymes (Jaaska 1978), electrophoresis of seedling proteins (Bahrman et al 1988), cpDNA (Bowman et al 1983;Ogihara and Tsunewaki 1988;Wang et al 1997), rRNA (Dvorak 1990), repetitive DNA sequences (Talbert et al 1991), variation in the restriction patterns of repeated nucleotide sequences (Dvorak and Zhang 1992), electrophoresis of leaf proteins (Mendlinger and Zohary 1995), nRFLP (Sasanuma et al 1996;Ciaffi et al 2000;Giorgi et al 2002), in situ hybridisation (Giorgi et al 2003), and CAPS on cpDNA (Haider and Nabulsi 2008).…”
Section: Genetic Relationships Among Triticum Speciessupporting
confidence: 86%
“…Although Sharma and Waines (1980) reported that tough rachis in Triticum monococcum (2n = 2x = 14) was controlled by contrasting alleles at 12 loci, Watanabe et al (2003) found that allelic variation at the Br 2 locus on chromosome 3A determined the rachis brittleness. The open-pollinated species, Aegilops speltoides (2n = 2x = 14; genome SS), which is the most likely source of the B genome of T. aestivum and T. durum (Sarker and Stebbins 1956;Dvorak and Appells 1982;Dvorak and Zhang 1990;Talbert et al 1991;Wang et al 1997), is composed of 2 morphological forms. In the form aucheri, whose spikes are conical, disarticulation occurs from stems at a single node at the bottom of the spikes, and only the terminal spikelet is awned.…”
Section: Mapping Of the Br 1 Locus (B 1 F 1 From Novosibirskaya 67*2/mentioning
confidence: 99%
“…The selection of the best varieties of wheat for domestication took place over many centuries in many regions. Today, only varieties of common, club and durum wheats are of commercial importance, but other species are still grown to suit local conditions and provide essential stock for formal breeding programs (Talbert et al 1991). Remains of both emmer and einkorn wheat have been found by archaeologists working on sites in the Middle East dating from the 7th millennium BC.…”
mentioning
confidence: 99%